2010
DOI: 10.2478/s11756-010-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase inhibition and antioxidant activity of selected forage crops

Abstract: The hypothesis of the possible therapeutic potential of selected species of forage crops is discussed. Extracts from genotypes of Anthyllis sp., Astragalus sp., Coronilla sp., Lotus sp., Medicago sp., Melilotus sp., Onobrychis sp. and Trifolium sp. were prepared and tested for proteinase inhibition and antioxidant activities. We found that Trifolium pratense accession POLKIE99-3 expressed the highest relative trypsin inhibition activity (80.0%) compared to standards. The highest thrombin inhibition activity (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Nevertheless both genotypes of buckwheats contain more polyphenols and flavonoids also due to a high content of the well-known flavonoid rutin (Jiang et al 2007), a compound typical and specific for this crop with well documented health beneficial effects. Achieved results are in rough correlation with papers published previously (Quettier-Deleu et al 2000;Ivanišová et al 2010) and our achieved results (Maliar et al 2011).…”
Section: Resultssupporting
confidence: 93%
“…Nevertheless both genotypes of buckwheats contain more polyphenols and flavonoids also due to a high content of the well-known flavonoid rutin (Jiang et al 2007), a compound typical and specific for this crop with well documented health beneficial effects. Achieved results are in rough correlation with papers published previously (Quettier-Deleu et al 2000;Ivanišová et al 2010) and our achieved results (Maliar et al 2011).…”
Section: Resultssupporting
confidence: 93%
“…In comparison with the extracts from hop ( Humulus lupulus L.) cones, the poppy grain extracts expressed approximately two times higher activities of IA_TR. On the contrary, IA_TR in alfalfa ( Medicago sativa L.) leaf extracts were the inhibitory activities two times lower. The highest IA_TY was found in the genotypes Redy , MS ZB‐3 and MS 423, while the lowest in the genotype Aristo ( Table ).…”
Section: Resultsmentioning
confidence: 95%
“…The highest IA_TY was found in the genotypes Redy , MS ZB‐3 and MS 423, while the lowest in the genotype Aristo ( Table ). An average value of IA_TY in poppy seeds was three times higher than in the extracts from hop cones, two times higher in comparison with oat seed extracts and also higher than in leaf extracts from alfalfa . The IA_UR of the 15 poppy genotypes were in the range of 31.0 – 51.8% ( Table ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, prunetin and pseudobaptigenin were detected in human plasma for the fi rst time. Maliar et al ( 2011 ) found that Trifolium pratense accession POLKIE99-3 expressed the highest relative trypsin inhibition activity (80.0 %) compared to standards. They also found that Trifolium pratense genetic resources SVKZAH98-40 possessed relatively high antioxidant properties.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 93%